Problem dyscypliny finansów publicznych w państwowej szkole wyższej. Zarys prawny - Ćwiąkała-Małys, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2007)
The public finance discipline should be treated as rigorous obeying law regulations governing rules and clauses of spending money and collecting budget profits. The most important condition of the public finance discipline in public high school is obeying law regulations concerning the distribution of public means. The law of the responsibility for the offending against the public finance discipline contains in 5–18 articles the offending against the public finance discipline items. This procedure guarantees a good management of public expenses and savings. A fulfilling the public finance discipline in high school is possible when the organs of high school as well as organizational and technical services take part in this process.
Keywords: szkolnictwo wyższe; finanse publiczne; finansowanie